Ideological Perlocutions of Palestinian and Israeli News on CNN Arabic Instagram (Pragmatic Cyber Study) - Khairunnisa, Annisa (Sunan Kalijaga: International Journal of Islamic Civilization, 2023)
The Palestine-Israel conflict has long been a deeply scrutinized subject, with social media playing a pivotal role in amplifying discussions around this complex issue. However, this dominant phenomenon has only been studied in aspects of discourse with a theoretical purpose. The concrete implications seen from perlocutions in the virtual realm have yet to be reviewed related to this phenomenon. Therefore, this research will reveal it with a pragmatic cyber approach. The research data included language features in the narrative of CNN Arabic Instagram posted throughout January 2022-May 2023. Data were collected using simak and sadap techniques and supplemented by descriptive and reflective notes. The data were analyzed with a pragmatic cyber perspective with a padan method correlating the comparison between lingual and extra-lingual elements. The results showed that in 17 posts throughout 2022-2023 with 40 data. 13 data (30%) found perlocutions to attract attention; 11 data (27%) perlocutions to arouse curiosity; 8 data (20%) perlocutions to distract; 5 data (10%) perlocutions to encourage; 2 data (5%) perlocutions to embarrass; and 1 data (2%) perlocution to frighten. This result indicates CNN Arabic's tendency to maintain Israel's image most subtly and tactically possible: to "attract attention".